Profibrotic effect of IL-17A and elevated IL-17RA in idiopathic pulmonary fibrosis and rheumatoid arthritis-associated lung disease support a direct role for IL-17A/IL-17RA in human fibrotic interstitial lung disease - Zhang, Jie; Wang, Dan; Wang, Lei; Wang, Shaohua; Roden, Anja C.; Zhao, Hao; Li, Xiujuan; Prakash, Y. S.; Matteson, Eric L.; Tschumperlin, Daniel J.; Vassallo, Robert (American journal of physiology. Lung cellular and molecular physiology, 2019)
Interleukin (IL)-17 is a T helper 17 cytokine implicated in the pathogenesis of many autoimmune diseases, including rheumatoid arthritis (RA). Although IL-17A has a well-established role in murine pulmonary fibrosis models, its role in the tissue remodeling and fibrosis occurring in idiopathic pulmonary fibrosis (IPF) and RA-associated interstitial lung disease (RA-ILD) is not very well defined. To address this question, we utilized complimentary studies to determine responsiveness of human normal and pathogenic lung fibroblasts to IL-17A and used lung biopsies acquired from patients with IPF and RA-ILD to determine IL-17A receptor (IL-17RA) expression. Both normal and pathogenic IPF lung fibroblasts express functional IL-17RA and respond to IL-17A stimulation with cell proliferation, generation of extracellular matrix (ECM) proteins, and induction of myofibroblast transdifferentiation. Small interfering RNA (siRNA) silencing of IL-17RA attenuated this fibroblast response to IL-17A on ECM production. These fibroblast responses to IL-17A are dependent on NF-κB-mediated signaling. In addition, inhibiting Janus activated kinase (JAK) 2 by either siRNA or a selective pharmacological inhibitor, AZD1480—but not a JAK1/JAK3 selective inhibitor, tofacitinib—also significantly reduced this IL-17A-induced fibrogenic response. Lung biopsies of RA-ILD patients demonstrate significantly higher IL-17RA expression in areas of fibroblast accumulation and fibrosis, compared with either IPF or normal lung tissue. These observations support a direct role for IL-17A in lung fibrosis that may be particularly relevant in the context of RA-ILD.